Variations in dynamic knee valgus and gluteus medius onset timing in non-athletic females related to hormonal changes during the menstrual cycle - Cesar, Guilherme Manna; Pereira, Vanessa Santos; Pereira Santiago, Paulo Roberto [UNESP]; Benze, Benedito Galvao; Lobo da Costa, Paula Hentshel; Amorim, Cesar Ferreira [UNESP]; Serrao, Fabio Viadanna (Elsevier B.V., 2011)
It has been suggested that activities of daily living could contribute to the occurrence of ACL injury in females. Currently, no studies have focused on the lower extremity behavior of a non-athletic population to compare or understand the lower extremity adeptness towards daily movements that mimic athletic tasks. Our hypothesis was that increased knee valgus angles would occur during the late follicular phase of the menstrual cycle accompanied by different onset timing of the gluteus medius muscle. In a controlled laboratory study, 23 non-athletic collegiate females participated and 15 subjects comprised the final sample for statistical analysis. Subjects performed a single leg drop landing maneuver while 3-D knee kinematics and gluteus medius muscle onset timing were assessed throughout three distinct phases of the menstrual cycle, confirmed by blood hormone analysis. In general, knee valgus angles were significantly less in the luteal phase compared to both follicular phases (p<0.005), while differences were not observed for gluteus medius onset timing (p = 0.936). As a decreased knee joint valgus angle was observed during the luteal phase, it was hypothesized that the hormone progesterone could significantly influence knee kinematics during a dynamic task. However, such influence was not observed for gluteus medius EMG onset timing as a significant correlation between gluteus medius onset timing and knee valgus angle could not be determined. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Dynamic valgus; Anterior cruciate ligament (ACL); Kinematics; Electromyography (EMG); Menstrual cycle